Association of diabetes with age-related macular degeneration in the EUREYE study. Issue 8 (7th May 2009) - Topouzis, F; Anastasopoulos, E; Augood, C; Bentham, G C; Chakravarthy, U; de Jong, P T V M; Rahu, M; Seland, J; Soubrane, G; Tomazzoli, L; Vingerling, J R; Vioque, J; et al.
Abstract : Objective: To examine the association between self-reported diabetes history and early or late age-related macular degeneration (AMD) in the European population. Methods: Participants aged 65 years and over in the cross-sectional population-based EUREYE study underwent an eye examination including digital retinal photography. The images were graded at a single centre. A structured questionnaire was administered by trained field workers for putative risk factors for AMD including history of diabetes mellitus. Logistic regression models were used to examine the association between diabetes and stages of AMD, taking account of potential demographic, behavioural, dietary and medical (history of cardiovascular disease) confounders. Main outcome measures: Photographic images were graded according to the modified International Classification System for AMD and stratified into five exclusive stages from no signs of AMD (AMD stage 0), early AMD (Stages 1–3) and late AMD (Stage 4). Late AMD was subdivided in neovascular AMD (NV-AMD) or geographic atrophy (GA). Results: Data on diabetes history and potential confounders were available in 2117 control subjects without AMD, 2182 with early AMD, 49 with GA and 101 with NV-AMD. Of all participants, 13.1% reported a history of diabetes. After adjusting for potential confounders, subjects with neovascular AMD compared with controls had increased odds for diabetes (odds ratio 1.81; 95% confidence interval, 1.10 to 2.98, p = 0.02). Subjects with AMD grades 1 to 3 or GA had no increased odds for diabetes compared with those without AMD. Conclusions: In the EUREYE study, after multiple adjustments, positive association of diabetes mellitus with neovascular AMD was found. The hypothesis that diabetes is associated with neovascular AMD but not with geographic atrophy may suggest a different pathogenesis of the two advanced forms of the disease and needs to be further evaluated.